Identifying vital nodes algorithm in social networks fusing higher-order information - Guanghui YAN; Meng ZHANG; Hao LUO; Shikui LI; Ting LIU (Tongxin xuebao)
Identifying vital nodes is a basic problem in complex network research.The existing theoretical framework,mainly considered from the lower-order structure of node-based and edge-based relations often ignores important factors such as interactivity and transitivity between multiple nodes.To identify vital nodes more accurately,the motif,the high-er-order structure of the network,was studied as the basic unit.Firstly,a notion of higher-order degree of nodes in a com-plex network was proposed.Then,the higher-order structure and lower-order structure of nodes were fused into evidence theory.A semi-local identifying vital nodes algorithm fusing higher-order information of nodes was designed.The results of experiments on three real social networks show that the proposed algorithm can identify vital nodes more accurately in the network than the existing methods which only focus on the low-order structure.